Sepsis in the critically ill patient: current and emerging management strategies. Issue 5 (4th May 2021) - Heming, Nicholas; Azabou, Eric; Cazaumayou, Xavier; Moine, Pierre; Annane, Djillali
ABSTRACT: Introduction : Sepsis, a dysregulated host response to infection, is a major cause of morbidity and mortality worldwide. Early identification and evidence-based treatment of sepsis are associated with improved outcomes. Areas covered : This narrative review was undertaken following a PubMed search for English language reports published before July 2020 using the terms 'sepsis, ' 'septic shock, ' 'fluids, ' 'fluid therapy, ' 'albumin, ' 'corticosteroids, ' 'vasopressor.' Emerging management strategies were identified following a search of the ClinicalTrails.gov database using the term 'sepsis.' Additional reports were identified by examining the reference lists of selected articles and based on personnel knowledge of the field of sepsis. Expert opinion : The core treatment of sepsis relies on source control, early antibiotics, and organ support. The main emerging strategies focus on immunomodulation, artificial intelligence, and on multi-omics approaches for a personalized therapy.